2018
DOI: 10.1186/s40066-018-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilizer rates on grain yield and nitrogen uptake and use efficiency of bread wheat (Triticum aestivum L.) varieties on the Vertisols of central highlands of Ethiopia

Abstract: Background: Nitrogen is one of the most important nutrients limiting yield of bread wheat in Ethiopian highlands. Application of a large amount of N fertilizer has been a method of increasing yield in the study area which is costly and can cause environmental pollution. Therefore, a field experiment was conducted for two consecutive years (2014 and 2015) to evaluate the effect of N application rates on grain yield, nitrogen uptake and N use efficiency of bread wheat varieties. The treatments consisted of a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
55
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 22 publications
25
55
2
Order By: Relevance
“…Prodip. Previous studies showed that the application of 150 kg/ha N resulted in increased plant height, spike length, number of spikelets per spike, weight of grains per spike, 1000 grain weight, grain yield and biological yield (Mandic et al, 2015;Adnan et al, 2016, Belete et al, 2018, which is in accordance with present findings. Research reported that higher grain yield (8.0 t/ha) was gained with the treatment receiving 240 kg N/ha than in control (3.9 kg/ha), 120 kg N/ha (4.4 t/ha), and 360 kg N/ha (6.5 t/ha) (Abedi et al, 2011), while grain yield was 5.81 t/ha due to the supplement of 160 kg N/ha in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prodip. Previous studies showed that the application of 150 kg/ha N resulted in increased plant height, spike length, number of spikelets per spike, weight of grains per spike, 1000 grain weight, grain yield and biological yield (Mandic et al, 2015;Adnan et al, 2016, Belete et al, 2018, which is in accordance with present findings. Research reported that higher grain yield (8.0 t/ha) was gained with the treatment receiving 240 kg N/ha than in control (3.9 kg/ha), 120 kg N/ha (4.4 t/ha), and 360 kg N/ha (6.5 t/ha) (Abedi et al, 2011), while grain yield was 5.81 t/ha due to the supplement of 160 kg N/ha in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrogen is the key nutrient element and plays an inevitable role to increase the tillering capacity which leads to higher yield potential. Optimum supply of nitrogen raises the nutritive value, protein content and improves the baking quality of wheat (Ames et al, 2003;Mandic et al, 2015).Application of nitrogen has considered as a primary means of increasing wheat grain yield as well as improves N uptake and N use efficiency and consequently nitrogen harvest index (Belete et al, 2018). Zinc (Zn) is an important metal component which is the functional, structural and regulatory cofactor of a large number of enzymes (Cakmak, 2008) and essential micronutrient which deficiency is common in wheat growing areas of Bangladesh, particularly in calcareous areas with high soil pH (Majd et al, 2015).Zinc deficiency severely reduces wheat production and nutritional quality of grains (Firdous et al, 2018).The functional role of Zn includes auxins metabolism, nitrogen metabolism and protection of cells against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…At Teton, NUE values were significantly affected by N fertilizer rate, and a stepwise decrease in NUE was noted as N rates increased. Belete, Dechassa, Molla, and Tana (2018) and Haile, Nigussie, and Ayana (2012) reported a decreasing trend in NUE with increasing N rates. At the Pondera site, although NUE was numerically higher for plots fertilized with the lowest N rate (28 kg N ha −1 , planted at the 67 kg ha −1 PLS seeding rate), overall, NUE values were comparable across applied N rates and the differences were not statistically significant ( Figure 6).…”
Section: Nitrogen Use Efficiencymentioning
confidence: 95%
“…In this regard, the biochar amendment is a viable strategy together with N fertilization. N application is key for increasing crop yields and biomass production (Ali, Khan, Imran, et al, 2019;Ali, Khan, Munsif, et al, 2019;Belete, Dechassa, Molla, & Tana, 2018;Lee, Wycislo, Guo, Lee, & Voigt, 2017).…”
Section: Introductionmentioning
confidence: 99%